Flexible Circuit Board
Patent Information
- Application Number
- JP2021061545
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-03-31
- Publication Date
- 2025-02-19
- Estimated Expiration
- 2041-03-31
AI Technical Summary
【0012】 ストリップライン構造の本発明のフレキシブル回路基板は、一対のグランド層の間で、信号用導体パターンを挟み込んでいる一対の第1樹脂フィルム及び第2樹脂フィルムのそれぞれのフィルム厚及びフィルム厚比と、並びに第1樹脂フィルム及び第2樹脂フィルムのそれぞれの引張弾性率と引張弾性率比とを、それぞれ特定範囲に限定している。このため、本発明のフレキシブル回路基板は、良好な耐90度折り曲げ性を示すことができる。よって、ミリ波アンテナ用RFケーブルとして有用である。
Smart Images

Figure 0007633071000008 
Figure 0007633071000009 
Figure 0007633071000010
Abstract
Description
[Technical field]
[0001] The present invention relates to a flexible circuit board. [Background technology]
[0002] One of the important applications of high-frequency flexible circuit boards is known as an RF cable for a millimeter-wave antenna. Flexible circuit boards (FPCs) for such RF cables generally have a structure (so-called stripline structure) in which a laminate is sandwiched between a pair of ground copper foils, the laminate being made of a first resin film as a dielectric, a signal conductor pattern formed thereon, and a second resin film laminated on the signal conductor pattern forming surface of the first resin film via an adhesive layer (see FIG. 1 of Patent Document 1).
[0003] In recent years, the housings of mobile electronic devices have become smaller and thinner, and when an RF cable for a millimeter-wave antenna is housed in the housing of a mobile electronic device, the RF cable is bent 90 degrees to house it in. For this reason, there is a demand for a stripline-structured RF cable for a millimeter-wave antenna to have good resistance to 90-degree bending. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] Patent No. 6537172 Summary of the Invention [Problem to be solved by the invention]
[0005] However, Patent Document 1 (particularly FIG. 1) only considers the dielectric characteristics of a flexible circuit board with a stripline structure, and does not consider at all the resistance to 90-degree bending that is required when such a flexible circuit board is used as an RF cable for a millimeter-wave antenna, for example.
[0006] An object of the present invention is to provide a flexible circuit board having the necessary resistance to bending at 90 degrees when the flexible circuit board having a stripline structure is used as an RF cable for a millimeter wave antenna, for example. [Means for solving the problem]
[0007] As a result of extensive research, the inventors have discovered that in a flexible circuit board having a stripline structure, the film thickness and film thickness ratio of a pair of first and second resin films sandwiching a signal conductor pattern between a pair of ground layers, as well as the tensile modulus and tensile modulus ratio of the first and second resin films, are closely related to the 90-degree bending resistance, and have completed the present invention.
[0008] That is, the present invention provides a flexible circuit board that is folded at approximately 90 degrees and stored in a housing of an electronic device, A first resin film; A conductive pattern formed on one surface of the first resin film; a first ground layer laminated on the other surface of the first resin film; a second resin film laminated on the conductive pattern forming surface side of the first resin film; a second ground layer laminated on a surface of the second resin film opposite to the first resin film, the thickness (L1) of the first resin film is within the range of 50 μm or more and 150 μm or less, the thickness (L2) of the second resin film is within the range of 50 μm or more and 150 μm or less, and the ratio (L2 / L1) of the thickness (L2) of the second resin film to the thickness (L1) of the first resin film is within the range of 0.8 or more and 1.2 or less, The flexible circuit board is characterized in that the tensile modulus of elasticity (M1) of the first resin film is within the range of 0.9 GPa or more and 7 GPa or less, the tensile modulus of elasticity (M2) of the second resin film is within the range of 0.9 GPa or more and 7 GPa or less, and the ratio (M2 / M1) of the tensile modulus of elasticity (M2) of the second resin film to the tensile modulus of elasticity (M1) of the first resin film is within the range of 0.7 or more and 1.3 or less.
[0009] In the flexible circuit board of the present invention, the second resin film has a polyimide insulating layer including a single or multiple polyimide layers and an adhesive layer, the adhesive layer is located between the polyimide insulating layer and a surface of the first resin film on which a conductor pattern is formed, The adhesive layer preferably has a tensile modulus of elasticity in the range of 0.2 GPa or more and 2 GPa or less.
[0010] In addition, in the flexible circuit board of the present invention, it is preferable that the first resin film has a polyimide layer (A) in the central layer, and the thickness of the polyimide layer (A) is in the range of 0.5 to 0.96 with respect to the total thickness of the first resin film.
[0011] In the flexible circuit board of the present invention, it is preferable that the second ground layer is bent at approximately 90 degrees so that the second ground layer is on the outside. Effect of the Invention
[0012] The flexible circuit board of the present invention having a stripline structure has a pair of first and second resin films sandwiching a signal conductor pattern between a pair of ground layers, and the film thickness and film thickness ratio of each of the first and second resin films, and the tensile elastic modulus and tensile elastic modulus ratio of each of the first and second resin films are each limited to a specific range. Therefore, the flexible circuit board of the present invention can exhibit good 90-degree bending resistance. Therefore, it is useful as an RF cable for a millimeter-wave antenna. [Brief description of the drawings]
[0013] [Figure 1] 1 is a schematic diagram showing a configuration of a flexible circuit board according to an embodiment of the present invention; [Diagram 2] FIG. 4 is a schematic diagram showing a configuration of a flexible circuit board according to another embodiment of the present invention. [Diagram 3] FIG. 4 is a schematic diagram showing a configuration of a flexible circuit board according to another embodiment of the present invention. [Figure 4] FIG. 4 is a schematic diagram showing a configuration of a flexible circuit board according to another embodiment of the present invention. [Diagram 5] This is a cross-sectional layer configuration diagram of a material model simulating an FPC. [Figure 6] FIG. 1 is a diagram illustrating the size of a material model simulating an FPC. [Figure 7] This is an explanatory diagram of the state in which an FPC is sandwiched between rigid bodies. [Figure 8] This is an explanatory diagram of the FPC bent at 90 degrees using a roller. [Figure 9] This is an explanatory diagram of the 90-degree bent state on the FPC simulation software. [Figure 10] FIG. 1 is a diagram illustrating a simulation step. [Figure 11] FIG. 2 is a schematic cross-sectional view of an FPC model applied to the simulation of Example 1. [Figure 12] FIG. 11 is a schematic cross-sectional view of an FPC model applied to the simulation of Example 2. [Figure 13] FIG. 11 is a schematic cross-sectional view of an FPC model applied to the simulation of Example 3. [Figure 14] FIG. 11 is a schematic cross-sectional view of an FPC model applied to the simulation of Example 4. [Figure 15] FIG. 13 is a schematic cross-sectional view of an FPC model applied to the simulation of Example 5. [Figure 16] 1 shows a stress-strain curve for insulating resin type A. [Figure 17] 1 shows a stress-strain curve of insulating resin type B. [Figure 18]1 shows a stress-strain curve of insulating resin type C. [Figure 19] 1 is a stress-strain curve of copper foil. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0014] DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS An embodiment of the present invention will be described with reference to the accompanying drawings.
[0015] [Structure of flexible circuit board] The flexible circuit board (FPC) of the present invention is folded at approximately 90 degrees and stored inside the housing of an electronic device, and examples of its configuration include those shown in Figures 1 to 4. The FPC 10 in Figure 1 has a first ground layer G1, a first resin film 1 laminated thereon, a conductor pattern S formed on the surface of the first resin film, a second resin film 2 laminated on the conductor pattern forming surface of the first resin film 1, and a second ground layer G2 laminated thereon.
[0016] The second resin film 2 may be composed of an adhesive layer 2a and a polyimide insulating layer 2b including a single layer or multiple polyimide layers, as shown in FIG. 2. In this case, the adhesive layer 2a is preferably disposed on the conductive pattern forming surface side of the first resin film 1. When the polyimide insulating layer 2b is formed of multiple polyimide layers, it may be composed of a polyimide layer 2b1 and a polyimide layer 2b2 as shown in FIG. 3, but is not limited to this structure. Here, the polyimide layer 2b1 and the polyimide layer 2b2 preferably have different characteristics in terms of blocking properties with the conductive pattern S and adhesive properties with the second ground layer, but may have the same characteristics.
[0017] On the other hand, the first resin film 1 may also be composed of a polyimide insulating layer having a single layer or multiple polyimide layers. For example, as shown in FIG. 4, the first resin film 1 may be composed of a polyimide layer (A) 1a in the center layer and a polyimide layer 1b and a polyimide layer 1c on both sides. In this case, the thickness of the polyimide layer (A) 1a is preferably 0.5 to 0.96, more preferably 0.5 to 0.8, relative to the total thickness of the first resin film 1. If the ratio of the thickness of the polyimide layer (A) 1a to the thickness of the first resin film 1 is below this range, the dielectric loss tangent of the first resin film 1 tends to be insufficient and sufficient dielectric properties tend not to be obtained, and if it exceeds this range, problems such as a decrease in the dimensional stability of the first resin film 1 tend to occur. Here, the central layer refers to the polyimide layer located exactly in the middle when the first resin film is composed of an odd number of polyimide layers (three or more), and when the first resin film is composed of an even number of polyimide layers (two or more), it is either of the two adjacent central polyimide layers, but it is preferable for it to be the layer closer to the first ground layer G1.
[0018] (Thickness of First Resin Film 1 and Second Resin Film 2) The thickness (L1) of the first resin film 1 and the thickness (L2) of the second resin film 2 constituting the FPC 10 of the present invention are each independently 50 μm or more and 150 μm or less, preferably 70 μm or more and 125 μm or less, in order to make the FPC 10 applicable to high frequency applications. If the thickness of the first resin film 1 is below this range, sufficient transmission characteristics are not exhibited, and if it exceeds this range, the thickness of the entire FPC becomes thick, resulting in low bending resistance. Also, if the thickness of the second resin film 2 is below this range, sufficient transmission characteristics are not exhibited, and if it exceeds this range, the thickness of the entire FPC becomes thick, resulting in low bending resistance.
[0019] In the FPC 10 of the present invention, the ratio (L2 / L1) of the thickness (L2) of the second resin film 2 to the thickness (L1) of the first resin film 1 is 0.8 to 1.2, preferably 0.9 to 1.1. If this ratio (L2 / L1) is below this range, when the FPC is bent 90 degrees, the neutral plane of bending shifts from the center of the copper foil in the thickness direction toward the first resin film side, increasing the maximum stress applied to the copper foil, whereas if it exceeds this range, the neutral plane shifts toward the second resin film side, increasing the maximum stress applied to the copper foil.
[0020] (Tensile Modulus of Elasticity of First Resin Film and Second Resin Film) In the FPC 10 of the present invention, the tensile modulus (M1) of the first resin film 1 and the tensile modulus (M2) of the second resin film 2 are each independently 0.9 GPa to 7 GPa, preferably 1 GPa to 7 GPa, and more preferably 1 GPa to 6 GPa. If the modulus is below this range, the rigidity of the FPC itself is reduced, decreasing the handleability when mounted on an electronic device, whereas if the modulus is above this range, the rigidity of the FPC itself is increased, which is one factor in decreasing the bending resistance.
[0021] In the FPC 10 of the present invention, the ratio (M2 / M1) of the tensile modulus (M2) of the second resin film 2 to the tensile modulus (M1) of the first resin film 1 is 0.7 to 1.3, preferably 0.8 to 1.2. If it is below this range, when the FPC is bent 90 degrees, the neutral plane of bending moves from the center in the thickness direction of the copper foil to the first resin film side, increasing the maximum stress applied to the copper foil, whereas if it is above this range, the neutral plane moves to the second resin film side, increasing the maximum stress applied to the copper foil.
[0022] When the second resin film 2 has an adhesive layer 2a as shown in Fig. 2, the tensile modulus of the adhesive layer is preferably 0.2 GPa to 2 GPa, more preferably 0.5 GPa to 1.5 GPa. If it is below this range, the adhesive tends to be difficult to handle in the FPC manufacturing process, and if it is above this range, it may affect the rigidity of the FPC itself, which may be a factor in reducing the flexibility of the FPC.
[0023] The tensile modulus of the first resin film 1 and the second resin film 2 can be measured using a commercially available tensile elasticity tester (for example, Strograph R-1 by Toyo Seiki Seisakusho Co., Ltd.) in an environment of a temperature of 23°C and a relative humidity of 50%. When the first resin film 1 and the second resin film 2 are composed of a plurality of polyimide layers and adhesive layers, the tensile modulus (M1 or M2) can be calculated according to the following formula, for example, when the first resin film 1 is composed of polyimide layers 1a, 1b, . . . 1n. Here, the total thickness of the first resin film 1 is L1 μm, the thickness of the polyimide layer 1a is L1a and the tensile modulus of the polyimide layer 1a alone is M1a, the thickness of the polyimide layer 1b is L1b and the tensile modulus of the polyimide layer 1a alone is M1b, and the thickness of the polyimide layer 1b is L1n and the tensile modulus of the polyimide layer 1n alone is M1n.
[0024]
number
[0025] (First ground layer and second ground layer) In the FPC 10 of the present invention, the first ground layer G1 and the second ground layer G2 are not particularly limited and may be made of any common FPC ground layer material, such as copper, stainless steel, iron, nickel, beryllium, aluminum, zinc, indium, silver, gold, tin, zirconium, tantalum, titanium, lead, magnesium, manganese, or other metal materials or alloy materials thereof. Among these, copper or copper alloys are particularly preferred.
[0026] The thickness of the first ground layer G1 and the second ground layer G2 is not particularly limited, and is preferably 5 μm to 30 μm, more preferably 10 μm to 20 μm, from the viewpoints of production stability, handling, FPC shielding performance, etc. When copper foil is used as the first ground layer G1 and the second ground layer G2, it may be rolled copper foil or electrolytic copper foil, or a commercially available copper foil may be used.
[0027] Furthermore, the metal or alloy material used for the first ground layer G1 and the second ground layer G2 may be subjected to a surface treatment using, for example, a siding agent, an aluminum alcoholate agent, an aluminum chelating agent, a silane coupling agent, etc., for the purpose of, for example, rust prevention treatment or improving adhesive strength. The first ground layer G1 and the second ground layer G2 may be subjected to conductor patterning by a known method, if necessary.
[0028] (Conductor pattern) In the FPC 10 of the present invention, the conductor pattern S functions as a signal line and can be appropriately selected from materials and configurations conventionally used as signal lines of FPCs, and can be made of the same material as the first ground layer G1 and the second ground layer G2. The patterning can be performed by a known method. The layer thickness of the conductor pattern S is not particularly limited, and is preferably 5 μm or more and 20 μm or less from the viewpoints of production stability, handling, transmission performance, etc.
[0029] (Materials of the first resin film and the second resin film) In the FPC 10 of the present invention, the first resin film 1 and the second resin film 2 are not particularly limited as long as they are made of a resin having electrical insulation properties, and examples thereof include polyimide, epoxy resin, phenol resin, polyethylene, polypropylene, polytetrafluoroethylene, silicone, and ethylene tetrafluoroethylene, but are preferably made of polyimide. The first resin film 1 and the second resin film 2 are not limited to a single layer, and may be a laminate of multiple resin layers, preferably multiple polyimide layers. In addition, when polyimide is used in the present invention, it means a resin made of a polymer having an imide group in the molecular structure, such as polyamideimide, polyetherimide, polyesterimide, polysiloxaneimide, and polybenzimidazoleimide, in addition to polyimide.
[0030] Hereinafter, a case where the first resin film and the second resin film are composed of a single layer or multiple polyimide layers will be described. Here, the polyimide constituting the polyimide layer contains tetracarboxylic acid residues derived from a tetracarboxylic dianhydride component and diamine residues derived from a diamine compound component, and from the viewpoint of storage modulus, they are generally divided into "thermoplastic polyimides" whose glass transition temperature (Tg) can be clearly confirmed, and "non-thermoplastic polyimides" which generally do not soften or show adhesiveness even when heated. Specifically, in the present invention, polyimides having a "storage modulus at 30°C" of 1.0 x 10 measured using a dynamic mechanical analyzer (DMA) are generally divided into "thermoplastic polyimides" whose storage modulus at 30°C is 1.0 x 10 8 Pa or more and the "storage modulus at 300°C" is 3.0×10 7 "Thermoplastic polyimide" has a storage modulus of less than 1.0 x 10 Pa and "storage modulus at 30°C" is 1.0 x 10 9 Pa or more and the "storage modulus at 300°C" is 3.0×10 8 They can be broadly divided into "thermoplastic polyimides" with a thermal conductivity of 100 Pa or more and "non-thermoplastic polyimides" with a thermal conductivity of 100 Pa or more.
[0031] When the first resin film 1 and the second resin film 2 are each a single polyimide layer, they may be made of a non-thermoplastic polyimide. However, it is preferable to make them of a thermoplastic polyimide which exhibits relatively better adhesion to the first ground layer G1, the second ground layer G2, and the conductor pattern S than non-thermoplastic polyimide.
[0032] In addition, when the first resin film 1 and the second resin film 2 are each composed of a plurality of polyimide layers, it is preferable to apply a thermoplastic polyimide to the layer that is in direct contact with the first ground layer G1, the second ground layer G2, or the conductor pattern S, and a non-thermoplastic polyimide that exhibits relatively better dielectric properties than a thermoplastic polyimide can be applied to the layer that is not in direct contact with the first ground layer G1, the second ground layer G2, or the conductor pattern S. For example, in the case of FIG. 2, a thermoplastic polyimide can be preferably applied to the adhesive layer 2a and the single-layer polyimide insulating layer 2b, and when the polyimide insulating layer 2b is composed of a plurality of polyimide layers 2b1 and a polyimide layer 2b2 as shown in FIG. 3, it is preferable to apply a thermoplastic polyimide to the polyimide layer 2b2 that is in contact with the second ground layer G2. In that case, a thermoplastic polyimide may be applied to the inner polyimide layer 2b1, but a good non-thermoplastic polyimide may also be applied. In the case of FIG. 4, it is preferable to use thermoplastic polyimides for the polyimide layers 1b and 1c, and a non-thermoplastic polyimide can be used for the polyimide layer (A) 1a. However, when the polyimide layer (A) 1a is used as a bonding sheet, it can be made of an adhesive polyimide which has enhanced film-forming properties and adhesiveness among thermoplastic polyimides, as described later.
[0033] (Non-thermoplastic polyimide) In the FPC 10 of the present invention, the non-thermoplastic polyimide applicable to the polyimide layer (A) 1a, the polyimide insulating layer 2b1, etc. preferably has a dianhydride residue derived from a dianhydride component containing an aromatic tetracarboxylic dianhydride component, and a diamine residue derived from a diamine component containing an aliphatic diamine and / or an aromatic diamine. As the dianhydride component and the diamine component, a monomer generally used in the synthesis of non-thermoplastic polyimides (see paragraphs
[0025] and
[0026] of JP 2014-141083 A and paragraphs
[0019] and
[0020] of JP 2016-72405 A) can be used. By selecting the type of the dianhydride component and the diamine component, and the respective molar ratios when two or more types of dianhydrides or diamines are used, the thermal expansion, adhesiveness, glass transition temperature, etc. of the polyimide can be controlled.
[0034] The non-thermoplastic polyimide preferably has an imide group concentration of 33% or less, more preferably 32% or less. If the imide group concentration exceeds 33%, the flame retardancy of the polyimide decreases, and the dielectric properties also deteriorate due to an increase in polar groups.
[0035] The thickness of the non-thermoplastic polyimide layer is preferably in the range of 6 μm to 100 μm, more preferably in the range of 9 μm to 50 μm, from the viewpoint of ensuring the function as a base layer and transportability during production and during thermoplastic polyimide coating. If the thickness of the non-thermoplastic polyimide layer is less than the lower limit, the electrical insulation and handling properties become insufficient, and if it exceeds the upper limit, the productivity decreases.
[0036] From the viewpoint of heat resistance, the non-thermoplastic polyimide preferably has a glass transition temperature (Tg) of 280° C. or higher, and more preferably 300° C. or higher.
[0037] From the viewpoint of suppressing warping, the thermal expansion coefficient of the non-thermoplastic polyimide is preferably 1 ppm / K or more and 30 ppm / K or less, more preferably 1 ppm / K or more and 25 ppm / K or less, and particularly preferably 15 ppm / K or more and 25 ppm / K or less.
[0038] Furthermore, the non-thermoplastic polyimide may be appropriately blended with optional components, such as plasticizers, other curable resin components such as epoxy resins, curing agents, curing accelerators, coupling agents, fillers, solvents, and flame retardants, within the scope of not impairing the effects of the invention.
[0039] (Thermoplastic polyimide) In the FPC 10 of the present invention, the thermoplastic polyimide preferably applicable to the polyimide layers 1b and 1c, the polyimide insulating layer 2b, the adhesive layer 2a, etc. has an acid dianhydride residue derived from an acid anhydride component containing an aromatic tetracarboxylic dianhydride component, and a diamine residue derived from a diamine component containing an aliphatic diamine and / or an aromatic diamine. As the acid dianhydride component and the diamine component, monomers generally used in the synthesis of thermoplastic polyimides (see JP2014-141083A, paragraphs
[0025] and
[0026] , and JP2016-72405A, paragraphs
[0019] and
[0020] ) can be used.
[0040] The thermoplastic polyimide preferably has an imide group concentration of 33% or less, more preferably 32% or less. If the imide group concentration exceeds 33%, the flame retardancy of the polyimide decreases, and the dielectric properties also deteriorate due to an increase in polar groups.
[0041] From the viewpoint of ensuring adhesive function, the thickness of the thermoplastic polyimide layer is preferably in the range of 1 μm to 10 μm, more preferably in the range of 1 μm to 5 μm. If the thickness of the thermoplastic polyimide layer is less than the lower limit, the adhesiveness becomes insufficient, and if it exceeds the upper limit, the dimensional stability tends to deteriorate.
[0042] From the viewpoint of suppressing warping, the thermal expansion coefficient of the thermoplastic polyimide is preferably 30 ppm / K or more, more preferably 30 ppm / K or more and 100 ppm / K or less, and particularly preferably 30 ppm / K or more and 80 ppm / K or less.
[0043] Furthermore, the thermoplastic polyimide may be appropriately blended with optional components, such as plasticizers, other curable resin components such as epoxy resins, curing agents, curing accelerators, inorganic fillers, coupling agents, bulking agents, solvents, and flame retardants, within the scope of the invention.
[0044] (adhesive layer) In the FPC 10 of the present invention, the adhesive layer 2a may be formed from the above-mentioned thermoplastic polyimide, but it can also be formed from an adhesive polyimide that can be used as a bonding sheet with improved adhesion and film-forming properties. The polyimide layer (A) 1a can also be formed from not only a non-thermoplastic polyimide, but also an adhesive polyimide that can be used as a bonding sheet.
[0045] (Tetracarboxylic acid residue of adhesive polyimide) The adhesive polyimide may contain, without particular limitation, tetracarboxylic acid residues derived from tetracarboxylic anhydrides generally used in thermoplastic polyimides, but preferably contains a total of 90 molar parts or more of tetracarboxylic acid residues derived from tetracarboxylic anhydrides represented by the following general formula (1) (hereinafter, sometimes referred to as "tetracarboxylic acid residues (1)") relative to 100 molar parts of the tetracarboxylic acid residues. By containing a total of 90 molar parts or more of tetracarboxylic acid residues (1) relative to 100 molar parts of the tetracarboxylic acid residues, it is easy to achieve both flexibility and heat resistance of the adhesive polyimide, which is preferable. If the total amount of tetracarboxylic acid residues (1) is less than 90 molar parts, the solvent solubility of the adhesive polyimide tends to decrease.
[0046] [ka]
[0047] In general formula (1), X represents a single bond or a divalent group selected from the following formulae:
[0048] [ka]
[0049] In the above formula, Z is -C6H4-, -(CH2) n or -CH2-CH(-OC(=O)-CH3)-CH2-, where n is an integer of 1 to 20.
[0050] Examples of tetracarboxylic acid dianhydrides for deriving the tetracarboxylic acid residue (1) include 3,3',4,4'-biphenyltetracarboxylic dianhydride (BPDA), 3,3',4,4'-benzophenonetetracarboxylic dianhydride (BTDA), 3,3',4,4'-diphenylsulfonetetracarboxylic dianhydride (DSDA), 4,4'-oxydiphthalic anhydride (ODPA), 4,4'-(hexafluoroisopropylidene)diphthalic anhydride (6FDA), 2,2-bis[4-(3,4-dicarboxyphenoxy)phenyl]propane dianhydride (BPADA), p-phenylenebis(trimellitic acid monoester anhydride) (TAHQ), and ethylene glycol bisanhydrotrimellitate (TMEG).
[0051] The adhesive polyimide may contain a tetracarboxylic acid residue derived from an acid anhydride other than the tetracarboxylic acid anhydride represented by the above general formula (1) within a range that does not impair the effects of the invention. Such tetracarboxylic acid residues are not particularly limited, but examples thereof include pyromellitic dianhydride, 1,4-phenylene bis(trimellitic acid monoester) dianhydride, 2,3',3,4'-biphenyl tetracarboxylic acid dianhydride, 2,2',3,3'- or 2,3,3',4'-benzophenone tetracarboxylic acid dianhydride, 2,3',3,4'-diphenyl ether tetracarboxylic acid dianhydride, bis(2,3-dicarboxyphenyl) ether dianhydride, 3,3',4,4'-, 2,3,3',4'- or 2,2',3,3'-p-terphenyl tetracarboxylic acid dianhydride, 2,2-bis(2,3- or 3,4-dicarboxyphenyl)-propane dianhydride, bis(2,3- or 3,4-dicarboxyphenyl)-propane dianhydride, and bis(2,3- or 3,4-dicarboxyphenyl)-propane dianhydride.4-dicarboxyphenyl)methane dianhydride, bis(2,3- or 3,4-dicarboxyphenyl)sulfone dianhydride, 1,1-bis(2,3- or 3,4-dicarboxyphenyl)ethane dianhydride, 1,2,7,8-, 1,2,6,7- or 1,2,9,10-phenanthrene-tetracarboxylic dianhydride, 2,3,6,7-anthracenetetracarboxylic dianhydride, 2,2-bis(3,4-dicarboxyphenyl)tetrafluoropropane dianhydride, 2,3,5,6-cyclohexane dianhydride, 1,2,5,6-naphthalenetetracarboxylic dianhydride, 1,4,5,8-naphthalenetetracarboxylic dianhydride, 2,3,6,7-naphthalenetetracarboxylic dianhydride, 4,8-dimethyl-1,2,3,5,6,7-hexahydronaphthalene-1,2 ,5,6-tetracarboxylic dianhydride, 2,6- or 2,7-dichloronaphthalene-1,4,5,8-tetracarboxylic dianhydride, 2,3,6,7-(or 1,4,5,8-)tetrachloronaphthalene-1,4,5,8-(or 2,3,6,7-)tetracarboxylic dianhydride, 2,3,8,9-, 3,4,9,10-, 4,5,10,11- or 5,6,11,12-perylene-tetracarboxylic dianhydride, cyclopentane-1,2,3,4-tetracarboxylic dianhydride, pyrazine-2,3,5,6-tetracarboxylic dianhydride, pyrrolidine-2,3,4,5-tetracarboxylic dianhydride, thiophene-2,3,4,5-tetracarboxylic dianhydride, 4,4'-bis(2,3-dicarboxyphenoxy)diphenylmethane dianhydride, ethylene glycol Examples of the tetracarboxylic acid residue include those derived from aromatic tetracarboxylic dianhydrides such as bisanhydrotrimellitate.
[0052] (Diamine residue of adhesive polyimide) The adhesive polyimide preferably contains 20 molar parts or more, more preferably 40 molar parts or more, and particularly preferably 60 molar parts or more of dimer acid type diamine residues derived from dimer acid type diamines per 100 molar parts of diamine residues. By containing the dimer acid type diamine residues in the above amount, the dielectric properties of the adhesive layer 2a etc. can be improved, and the thermocompression bonding properties can be improved by lowering the glass transition temperature (lowering Tg) of the adhesive layer, and the internal stress can be alleviated by lowering the elastic modulus. If the dimer acid type diamine residues are less than 20 molar parts per 100 molar parts of diamine residues, sufficient adhesiveness as an adhesive layer may not be obtained, and the elastic modulus of the adhesive layer, which has high thermal expansion, may increase, which may deteriorate the dimensional change rate after the formation of the conductor pattern S.
[0053] Here, the dimer acid type diamine means a diamine in which two terminal carboxylic acid groups (-COOH) of a dimer acid are replaced by primary aminomethyl groups (-CH2-NH2) or amino groups (-NH2). Dimer acid is a known dibasic acid obtained by intermolecular polymerization reaction of unsaturated fatty acids, and its industrial production process is almost standardized in the industry, and is obtained by dimerizing unsaturated fatty acids having 11 to 22 carbon atoms using a clay catalyst or the like. Industrially obtained dimer acid is mainly composed of a dibasic acid having 36 carbon atoms obtained by dimerizing unsaturated fatty acids having 18 carbon atoms such as oleic acid and linoleic acid, but contains arbitrary amounts of monomer acid (having 18 carbon atoms), trimer acid (having 54 carbon atoms), and other polymerized fatty acids having 20 to 54 carbon atoms depending on the degree of purification. In the present invention, it is preferable to use dimer acid whose dimer acid content has been increased to 90% by weight or more by molecular distillation. Furthermore, although double bonds remain after the dimerization reaction, in the present invention, those which have been further subjected to a hydrogenation reaction to reduce the degree of unsaturation are also included in the dimer acid.
[0054] As a feature of the dimer acid type diamine, the polyimide can be endowed with the characteristics derived from the dimer acid skeleton. That is, since the dimer acid type diamine is an aliphatic macromolecule with a molecular weight of about 560 to 620, the molar volume of the molecule can be increased and the polar group of the polyimide can be relatively reduced. It is considered that such a feature of the dimer acid type diamine contributes to improving the dielectric properties by reducing the dielectric constant and the dielectric loss tangent while suppressing the deterioration of the heat resistance of the polyimide. In addition, since it has two freely moving hydrophobic chains with 7 to 9 carbon atoms and two chain-like aliphatic amino groups with a length close to 18 carbon atoms, not only can it give flexibility to the polyimide, but it can also make the polyimide have an asymmetric chemical structure or a non-planar chemical structure, so it is considered that it is possible to reduce the dielectric constant and the dielectric loss tangent of the polyimide.
[0055] Dimer acid diamines are commercially available, such as PRIAMINE 1073 (trade name), PRIAMINE 1074 (trade name), and PRIAMINE 1075 (trade name) manufactured by Croda Japan, and VERSAMINE 551 (trade name) and VERSAMINE 552 (trade name) manufactured by BASF Japan.
[0056] In addition, the adhesive polyimide preferably contains a diamine residue derived from at least one diamine compound selected from the diamine compounds represented by the following general formulas (B1) to (B7) in a total amount of 20 to 80 mol parts, more preferably 20 to 60 mol parts, relative to 100 mol parts of the total diamine components. Since the diamine compounds represented by the general formulas (B1) to (B7) have a molecular structure with flexibility, the flexibility of the polyimide molecular chain can be improved and thermoplasticity can be imparted by using at least one diamine compound selected from these in an amount within the above range. If the total amount of the diamine compounds represented by the general formulas (B1) to (B7) exceeds 80 mol parts relative to 100 mol parts of the total diamine components, the flexibility of the polyimide becomes insufficient and Tg increases, so that the residual stress due to thermocompression bonding increases and the dimensional change rate after etching tends to deteriorate.
[0057] [ka]
[0058] In formulae (B1) to (B7), R1 independently represents a monovalent hydrocarbon group or alkoxy group having 1 to 6 carbon atoms, linking group A independently represents a divalent group selected from -O-, -S-, -CO-, -SO-, -SO2-, -COO-, -CH2-, -C(CH3)2-, -NH- or -CONH-, and n1 independently represents an integer of 0 to 4, with the proviso that formula (B3) does not overlap with formula (B2), and formula (B5) does not overlap with formula (B4).
[0059] Here, "independently" means that in one or more of the above formulae (B1) to (B7), multiple linking groups A, multiple R1s, or multiple n1s may be the same or different. In addition, in the formulae (B1) to (B7), the hydrogen atoms in the two terminal amino groups may be substituted, for example, -NR2R3 (wherein R2 and R3 are independently any substituent such as an alkyl group).
[0060] The diamine represented by formula (B1) (hereinafter, sometimes referred to as "diamine (B1)") is an aromatic diamine having two benzene rings. In this diamine (B1), since at least one amino group directly bonded to the benzene ring and the divalent linking group A are at the meta position, the degree of freedom of the polyimide molecular chain is increased, resulting in high flexibility, which is considered to contribute to improving the flexibility of the polyimide molecular chain. Therefore, by using diamine (B1), the thermoplasticity of the polyimide is increased. Here, the linking group A is preferably -O-, -CH2-, -C(CH3)2-, -CO-, -SO2-, -S-, or -COO-.
[0061] Examples of the diamine (B1) include 3,3'-diaminodiphenylmethane, 3,3'-diaminodiphenylpropane, 3,3'-diaminodiphenyl sulfide, 3,3'-diaminodiphenyl sulfone, 3,3-diaminodiphenyl ether, 3,4'-diaminodiphenyl ether, 3,4'-diaminodiphenylmethane, 3,4'-diaminodiphenylpropane, 3,4'-diaminodiphenyl sulfide, 3,3'-diaminobenzophenone, and (3,3'-bisamino)diphenylamine.
[0062] The diamine represented by formula (B2) (hereinafter sometimes referred to as "diamine (B2)") is an aromatic diamine having three benzene rings. In this diamine (B2), the amino group directly bonded to at least one benzene ring and the divalent linking group A are at the meta position, so that the degree of freedom of the polyimide molecular chain is increased and the polyimide molecular chain has high flexibility, which is thought to contribute to improving the flexibility of the polyimide molecular chain. Therefore, by using diamine (B2), the thermoplasticity of the polyimide is increased. Here, the linking group A is preferably -O-.
[0063] Examples of the diamine (B2) include 1,4-bis(3-aminophenoxy)benzene, 3-[4-(4-aminophenoxy)phenoxy]benzeneamine, and 3-[3-(4-aminophenoxy)phenoxy]benzeneamine.
[0064] The diamine represented by formula (B3) (hereinafter, sometimes referred to as "diamine (B3)") is an aromatic diamine having three benzene rings. In this diamine (B3), two divalent linking groups A directly bonded to one benzene ring are in meta positions with respect to each other, so that the degree of freedom of the polyimide molecular chain is increased and the polyimide molecular chain has high flexibility, which is considered to contribute to improving the flexibility of the polyimide molecular chain. Therefore, by using diamine (B3), the thermoplasticity of the polyimide is increased. Here, as the linking group A, -O- is preferable.
[0065] Examples of diamine (B3) include 1,3-bis(4-aminophenoxy)benzene (TPE-R), 1,3-bis(3-aminophenoxy)benzene (APB), 4,4'-[2-methyl-(1,3-phenylene)bisoxy]bisaniline, 4,4'-[4-methyl-(1,3-phenylene)bisoxy]bisaniline, and 4,4'-[5-methyl-(1,3-phenylene)bisoxy]bisaniline.
[0066] The diamine represented by formula (B4) (hereinafter, sometimes referred to as "diamine (B4)") is an aromatic diamine having four benzene rings. This diamine (B4) has high flexibility because at least one amino group directly bonded to the benzene ring and the divalent linking group A are at the meta position, which is considered to contribute to improving the flexibility of the polyimide molecular chain. Therefore, the use of diamine (B4) enhances the thermoplasticity of the polyimide. Here, the linking group A is preferably -O-, -CH2-, -C(CH3)2-, -SO2-, -CO-, or -CONH-.
[0067] Examples of the diamine (B4) include bis[4-(3-aminophenoxy)phenyl]methane, bis[4-(3-aminophenoxy)phenyl]propane, bis[4-(3-aminophenoxy)phenyl]ether, bis[4-(3-aminophenoxy)phenyl]sulfone, bis[4-(3-aminophenoxy)]benzophenone, and bis[4,4'-(3-aminophenoxy)]benzanilide.
[0068] The diamine represented by formula (B5) (hereinafter, sometimes referred to as "diamine (B5)") is an aromatic diamine having four benzene rings. This diamine (B5) is a polyamine having two divalent linking groups A directly bonded to at least one benzene ring at meta positions relative to each other. The degree of freedom of the imide molecular chain is increased, and it has high flexibility, which is thought to contribute to improving the flexibility of the polyimide molecular chain. Therefore, by using the diamine (B5), the thermoplasticity of the polyimide is increased. Here, the linking group A is preferably -O-.
[0069] Examples of the diamine (B5) include 4-[3-[4-(4-aminophenoxy)phenoxy]phenoxy]aniline, 4,4'-[oxybis(3,1-phenyleneoxy)]bisaniline, and the like.
[0070] The diamine represented by formula (B6) (hereinafter sometimes referred to as "diamine (B6)") is an aromatic diamine having four benzene rings. This diamine (B6) has high flexibility due to having at least two ether bonds, and is considered to contribute to improving the flexibility of the polyimide molecular chain. Therefore, the use of diamine (B6) enhances the thermoplasticity of the polyimide. Here, the linking group A is preferably -C(CH3)2-, -O-, -SO2-, or -CO-.
[0071] Examples of diamines (B6) include 2,2-bis[4-(4-aminophenoxy)phenyl]propane (BAPP), bis[4-(4-aminophenoxy)phenyl]ether (BAPE), bis[4-(4-aminophenoxy)phenyl]sulfone (BAPS), and bis[4-(4-aminophenoxy)phenyl]ketone (BAPK).
[0072] The diamine represented by formula (B7) (hereinafter sometimes referred to as "diamine (B7)") is an aromatic diamine having four benzene rings. This diamine (B7) has a highly flexible divalent linking group A on both sides of the diphenyl skeleton, which is believed to contribute to improving the flexibility of the polyimide molecular chain. Therefore, the use of diamine (B7) enhances the thermoplasticity of the polyimide. Here, the linking group A is preferably -O-.
[0073] Examples of the diamine (B7) include bis[4-(3-aminophenoxy)]biphenyl, bis[4-(4-aminophenoxy)]biphenyl, and the like.
[0074] The adhesive polyimide may contain a diamine residue derived from a diamine compound other than the above dimer acid type diamine and diamines (B1) to (B7) within the scope of the invention. As the diamine residue derived from a diamine compound other than the above dimer acid type diamine and diamines (B1) to (B7), any diamine compound generally used in thermoplastic polyimides may be used without limitation.
[0075] In the adhesive polyimide, the thermal expansion coefficient, tensile modulus, glass transition temperature, etc. can be controlled by selecting the types of the tetracarboxylic acid residues and diamine residues, and when two or more types of tetracarboxylic acid residues or diamine residues are used, respectively. When the adhesive polyimide has a plurality of polyimide structural units, they may be present as blocks or randomly, but are preferably present randomly.
[0076] The imide group concentration of the adhesive polyimide is preferably 20% by weight or less. Here, "imide group concentration" means the value obtained by dividing the molecular weight of the imide group (-(CO)2-N-) in the polyimide by the molecular weight of the entire polyimide structure. If the imide group concentration exceeds 20% by weight, the molecular weight of the resin itself decreases, and the low moisture absorption property deteriorates due to an increase in polar groups, and Tg and elastic modulus increase.
[0077] The weight-average molecular weight of the adhesive polyimide is, for example, preferably in the range of 10,000 to 400,000, more preferably in the range of 20,000 to 350,000. If the weight-average molecular weight is less than 10,000, the strength of the adhesive layer 2a tends to decrease and become brittle. On the other hand, if the weight-average molecular weight exceeds 400,000, the viscosity increases excessively, and defects such as uneven thickness and streaks in the adhesive layer 2a tend to occur during the coating process.
[0078] The adhesive polyimide is most preferably a completely imidized structure. However, a part of the polyimide may be an amic acid. The imidization rate can be determined by measuring the infrared absorption spectrum of the polyimide thin film by a single reflection ATR method using a Fourier transform infrared spectrophotometer (commercially available: FT / IR620 manufactured by JASCO Corporation) at 1015 cm -1 Based on the benzene ring absorber near 1780cm -1 It can be calculated from the absorbance of the C=O stretching derived from the imide group.
[0079] (Cross-linking in adhesive polyimides) When the adhesive polyimide has a ketone group, the ketone group can be reacted with the amino group of an amino compound having at least two primary amino groups as functional groups to form a C=N bond, thereby forming a crosslinked structure. The heat resistance of the adhesive polyimide can be improved by forming a crosslinked structure. A preferred tetracarboxylic anhydride for forming an adhesive polyimide having a ketone group is, for example, 3,3',4,4'-benzophenonetetracarboxylic dianhydride (BTDA), and a preferred diamine compound is, for example, an aromatic diamine such as 4,4'-bis(3-aminophenoxy)benzophenone (BABP) or 1,3-bis[4-(3-aminophenoxy)benzoyl]benzene (BABB).
[0080] Examples of amino compounds that can be used to crosslink adhesive polyimides include dihydrazide compounds, aromatic diamines, and aliphatic amines. Among these, dihydrazide compounds are preferred. Aliphatic amines other than dihydrazide compounds are prone to form crosslinked structures even at room temperature, which raises concerns about the storage stability of the varnish, while aromatic diamines require high temperatures to form crosslinked structures. In this way, when a dihydrazide compound is used, it is possible to achieve both the storage stability of the varnish and a shortened curing time. Examples of dihydrazide compounds include oxalic acid dihydrazide, malonic acid dihydrazide, succinic acid dihydrazide, glutaric acid dihydrazide, adipic acid dihydrazide, pimelic acid dihydrazide, suberic acid dihydrazide, azelaic acid dihydrazide, sebacic acid dihydrazide, dodecanedioic acid dihydrazide, maleic acid dihydrazide, fumaric acid dihydrazide, diglyceryl ester dihydrazide, ... Preferred are dihydrazide compounds such as cholic acid dihydrazide, tartaric acid dihydrazide, malic acid dihydrazide, phthalic acid dihydrazide, isophthalic acid dihydrazide, terephthalic acid dihydrazide, 2,6-naphthoedioic acid dihydrazide, 4,4-bisbenzene dihydrazide, 1,4-naphthoic acid dihydrazide, 2,6-pyridine diacid dihydrazide, itaconic acid dihydrazide, etc. The above dihydrazide compounds may be used alone or in combination of two or more.
[0081] The adhesive polyimide can be produced by reacting the above-mentioned tetracarboxylic dianhydride with a diamine compound in a solvent, generating a polyamic acid, and then heating to close the ring. For example, the tetracarboxylic dianhydride and the diamine compound are dissolved in an organic solvent in approximately equal moles, and the mixture is stirred at a temperature in the range of 0 to 100°C for 30 minutes to 24 hours to cause a polymerization reaction, thereby obtaining a polyamic acid, which is a precursor of the polyimide. In the reaction, the reaction components are dissolved in the organic solvent so that the generated precursor is in the range of 5 to 50% by weight, preferably in the range of 10 to 40% by weight. Examples of organic solvents used in the polymerization reaction include N,N-dimethylformamide (DMF), N,N-dimethylacetamide (DMAc), N,N-diethylacetamide, N-methyl-2-pyrrolidone (NMP), 2-butanone, dimethylsulfoxide (DMSO), hexamethylphosphoramide, N-methylcaprolactam, dimethyl sulfate, cyclohexanone, dioxane, tetrahydrofuran, diglyme, triglyme, and cresol. Two or more of these solvents can be used in combination, and aromatic hydrocarbons such as xylene and toluene can also be used in combination. The amount of such organic solvents is not particularly limited, but it is preferable to adjust the amount of the organic solvent to be used so that the concentration of the polyamic acid solution obtained by the polymerization reaction is about 5 to 50% by weight.
[0082] The synthesized polyamic acid is usually advantageously used as a reaction solvent solution, but can be concentrated, diluted, or replaced with another organic solvent if necessary. Polyamic acid is generally advantageously used because it has excellent solvent solubility. The viscosity of the polyamic acid solution is preferably within the range of 500 cps to 100,000 cps. If it is outside this range, for example, defects such as uneven thickness and streaks are likely to occur in the film during coating work using a coater or the like.
[0083] The method for imidizing the polyamic acid to form the adhesive polyimide is not particularly limited, and for example, a heat treatment in which the polyamic acid is heated in the above-mentioned solvent at a temperature in the range of 80 to 400° C. for 1 to 24 hours is preferably used.
[0084] When the adhesive polyimide obtained as described above is crosslinked, the above amino compound is added to a resin solution containing an adhesive polyimide having a ketone group, and the ketone group in the adhesive polyimide and the primary amino group of the amino compound are condensed. This condensation reaction causes the resin solution to harden and become a hardened product. In this case, the amount of the amino compound added is such that the total amount of the primary amino group is 0.004 mol to 1.5 mol, preferably 0.005 mol to 1.2 mol, more preferably 0.03 mol to 0.9 mol, and most preferably 0.04 mol to 0.5 mol per mol of the ketone group. When the amount of amino compound added is such that the total number of primary amino groups per mole of ketone groups is less than 0.004 moles, crosslinking of the adhesive polyimide by the amino compound is insufficient, and the adhesive layer after curing tends not to exhibit heat resistance. When the amount of amino compound added exceeds 1.5 moles, the unreacted amino compound acts as a thermoplasticizer, tending to reduce the heat resistance of the adhesive layer 2a and the polyimide layer 1a.
[0085] The conditions of the condensation reaction for forming crosslinks are not particularly limited as long as the ketone group in the adhesive polyimide reacts with the primary amino group of the amino compound to form an imine bond (C=N bond). The temperature of the heat condensation is preferably within the range of, for example, 120 to 220°C, more preferably within the range of 140 to 200°C, for the purpose of releasing water produced by condensation out of the system, or for the purpose of simplifying the condensation step when the heat condensation reaction is carried out subsequently to the synthesis of the adhesive polyimide. The reaction time is preferably about 30 minutes to 24 hours, and the end point of the reaction is determined by measuring the infrared absorption spectrum using, for example, a Fourier transform infrared spectrophotometer (commercially available: FT / IR620 manufactured by JASCO Corporation) at 1670 cm. -1 The decrease or disappearance of the absorption peak due to the ketone group in the polyimide resin near 1635 cm -1 This can be confirmed by the appearance of an absorption peak derived from a nearby imine group.
[0086] The thermal condensation of the ketone group of the adhesive polyimide and the primary amino group of the amino compound can be carried out, for example, by (a) adding an amino compound and heating following the synthesis (imidization) of the adhesive polyimide, (b) charging an excess amount of an amino compound as a diamine component in advance, and heating the adhesive polyimide together with the remaining amino compound not involved in imidization or amidation following the synthesis (imidization) of the adhesive polyimide, or (c) processing the adhesive polyimide composition to which the amino compound has been added into a predetermined shape (for example, after applying it to any substrate or forming it into a film) and then heating it, or the like.
[0087] In the above description, the formation of imine bonds is used to form a crosslinked structure in order to impart heat resistance to the adhesive polyimide. However, the present invention is not limited to this method. For example, the adhesive polyimide can be cured by blending an epoxy resin, an epoxy resin curing agent, or the like.
[0088] By using the adhesive polyimide obtained as described above, the adhesive layer 2a and the polyimide layer 1a have excellent flexibility and dielectric properties (low dielectric constant and low dielectric tangent). As described later, the adhesive polyimide has a sufficiently low storage modulus in the temperature range of about 100° C., so that the adhesion temperature can be significantly lowered compared to other adhesive resins such as fluorine-based resins.
[0089] <Glass transition temperature (Tg) of adhesive polyimide> The adhesive polyimide preferably has a glass transition temperature (Tg) of 250° C. or less, more preferably in the range of 40° C. to 200° C. By making the Tg of the adhesive polyimide 250° C. or less, thermocompression bonding at a low temperature is possible, and the internal stress generated during lamination can be alleviated, and dimensional change after circuit processing can be suppressed. If the Tg of the adhesive polyimide exceeds 250° C., the temperature required for lamination to another polyimide layer becomes high, and dimensional stability after circuit processing may be impaired.
[0090] <Storage modulus of adhesive polyimide> The adhesive polyimide satisfies the storage elastic modulus of the thermoplastic polyimide defined in this specification, and further has a temperature range in which the storage elastic modulus decreases steeply with increasing temperature in the range of 40 to 250 °C. Such characteristics of the adhesive polyimide are considered to be factors that relieve the internal stress during thermocompression bonding and maintain the dimensional stability after circuit processing. The storage elastic modulus of the adhesive polyimide at the upper limit temperature of the temperature range is preferably 5×10 7 Pa or less, more preferably in the range of 1×10 5 to 5×10 7 Pa. By setting the storage elastic modulus in such a manner, even if it is the upper limit of the above temperature range, thermocompression bonding can be performed at 250 °C or lower, ensuring adhesion and suppressing dimensional changes after circuit processing.
[0091] <Dielectric Tangent of the First Resin Film and the Second Resin Film> In the first resin film 1 and the second resin film 2, in order to suppress the deterioration of dielectric loss, the dielectric tangent (Tanδ) at 10 GHz is preferably 0.02 or less, more preferably 0.01 or less, and still more preferably 0.008 or less. When the dielectric tangent exceeds 0.02, when applied to a circuit board, inconveniences such as loss of electrical signals on the transmission path of high-frequency signals are likely to occur. The lower limit value of the dielectric tangent at 10 GHz is not particularly limited, but can be determined in consideration of the physical property control as the insulating resin layer of the circuit board.
[0092] <Relative Dielectric Constant of the First Resin Film and the Second Resin Film> In the first resin film 1 and the second resin film 2, as a whole, the relative dielectric constant at 10 GHz is preferably 4.0 or less, more preferably 3.5 or less, and still more preferably 3.2 or less. When the dielectric constant at 10 GHz exceeds 4.0, when applied to a circuit board, it leads to deterioration of dielectric loss, and inconveniences such as loss of electrical signals on the transmission path of high-frequency signals are likely to occur.
[0093] <Flexibility of the FPC in 90-degree Bending> In the present invention, the 90-degree bending resistance of an FPC can be evaluated in principle by repeatedly bending the FPC 90 degrees and measuring the number of bending times until the FPC breaks. In the present invention, however, the 90-degree bending resistance can be evaluated by performing a 90-degree bending simulation of the FPC for the conductor pattern set in the inner layer of the FPC model, and calculating the maximum strain generated in the conductor pattern of the FPC model using a known finite element analysis tool (for example, the general-purpose nonlinear analysis solver Marc). It can be said that the lower the maximum strain, the better the 90-degree bending resistance. In the examples described later, a specific example of a simulation of the 90-degree bending resistance of an FPC will be described.
[0094] [Manufacturing of flexible circuit boards] The flexible circuit board of the present invention can be manufactured by a conventional method. For example, an adhesive layer is formed on a release film as a resin sheet. Separately, a single-sided metal-clad laminate consisting of a metal layer / polyimide layer is prepared by applying and drying a single or multiple polyamide solutions on a metal layer. Next, a resin sheet is attached to the polyimide layer of the single-sided metal-clad laminate, and then the release sheet is removed, and a metal layer is attached to the exposed resin sheet, and patterned to form a conductor pattern. A new resin sheet is attached to the conductor pattern, and a polyimide layer of another single-sided metal-clad laminate is further attached to produce a flexible circuit board as shown in FIG. 1. The flexible circuit board of the present invention can also be manufactured by a method other than that described above. EXAMPLES
[0095] The present invention will be described in detail below with reference to examples, but the present invention is not limited to these examples. In the following examples and comparative examples, a simulation model of an FPC was prepared, and the simulation was performed using the finite element method (FEM), and analysis was performed using shell elements. The following is a more detailed description.
[0096] [Mechanical simulation in the elastic-plastic region] Using shell elements in a finite element analysis tool (general-purpose nonlinear analysis solver Marc), a finite element analysis model simulating a 90-degree bending test of an FPC is constructed from the Young's modulus and plastic strain-stress relationship of the material obtained from the stress-strain relationship of each material obtained from a uniaxial extension tensile test, and a nonlinear structural analysis is performed to find a solution for the strain field that occurs in the FPC (focusing on the inner layer signal copper wiring) when the rigid body in the finite element analysis model is forcibly displaced.
[0097] [Simulation model] The finite element analysis model includes a material model (Fig. 5) that simulates an FPC created using shell elements, a rectangular rigid body for fixing the FPC (Fig. 7), and a rolled rigid body for bending the FPC (Fig. 8). That is, as shown in Fig. 7, the FPC is fixed with a rectangular rigid body for fixing it, and as shown in Fig. 8, the rolled rigid body for bending the FPC is moved and brought into contact with the FPC to bend the FPC 90 degrees, and the solution for the strain field generated in the FPC at this time is obtained. Figure 9 shows the actual 90-degree bent state on the simulation software.
[0098] The dimensional elements of the material model simulating an FPC with a stripline structure are as shown in Fig. 6: the signal copper wiring width is 2 mm, the signal copper wiring height is 20 μm, the ground copper wiring on both the top and bottom sides is 12 μm each, the signal wiring is located in the center of the FPC width direction, and the overall width of the FPC is 10 mm.
[0099] [Simulation flow] The flow of the simulation applied to this embodiment is shown in Fig. 10. This flow includes at least the steps of creating a simulation model, inputting physical property data, performing a 90-degree bending simulation, and calculating the maximum distortion occurring in the signal copper wiring, in this order.
[0100] In the "step of creating a simulation model", an FPC model to be applied to the simulation and an equipment model for bending the FPC 90 degrees (FPC clamping jig, FPC bending roller device, etc.) are created. In the "step of inputting physical property data", the physical property values of each model required for the simulation calculations, such as elastic modulus, yield stress, and strain-stress curve, are input into the simulation software. In the "step of performing a 90-degree bending simulation", as shown in Figure 9, an FPC is actually bent 90 degrees using the simulation software. As a result of this, in the subsequent "step of calculating the maximum strain generated in the signal copper wiring", the relationship between stress and strain in the signal copper wiring of the FPC is calculated, and the maximum strain is calculated.
[0101] [Measurement of stress-strain curve] The tensile modulus required for the calculation of the simulation was measured under an environment of a temperature of 23°C and a relative humidity of 50% using a Strograph R-1 manufactured by Toyo Seiki Seisakusho Co., Ltd. The measurement sample used had a MD of 250 mm x TD of 12.7 mm, and was measured under the conditions of a load cell of 500 N, a tensile speed of 50 mm / min, and a chuck distance of 50 mm.
[0102] [Calculation of average tensile modulus] The tensile modulus of each insulator layer is measured, and the average tensile modulus is calculated using the thickness ratio of the resin laminate composed of different insulators. When n types of different insulators are present in a range of 5 μm, the elastic modulus M1 [GPa], thickness T1 [μm], elastic modulus M2 [GPa], thickness T2 [μm], and elastic modulus M n [GPa], thickness T n Using the numerical value in [μm], the average elastic modulus is calculated by the following formula.
[0103]
number
[0104] [Comparative Example 1] In the laminate shown in Fig. 11, the thicknesses of the insulating resins were (A) 25 μm, (B) 25 μm, and (C) 50 μm, and the resin types were (A): Type A, (B): Type B, and (C): Type A. The thicknesses of the ground and signal copper wiring were 12 μm and 20 μm, respectively, and the copper foil type was copper foil 1 for all.
[0105] [Example 1] In the laminate shown in Fig. 12, the thicknesses of the insulating resins were (A) 50 μm, (B) 25 μm, (C) 25 μm, (D) 25 μm, and (E) 25 μm, and the resin types were (A): Type A, (B): Type B, (C): Type A, (D): Type B, and (E): Type A. The thicknesses of the ground and signal copper wiring were 12 μm and 20 μm, respectively, and the copper foil type was copper foil 1 for all.
[0106] [Example 2] In the laminate shown in Fig. 13, the thicknesses of the insulating resins were (a) 50μm, (b) 25μm, (c) 25μm, (d) 37.5μm, (e) 25μm, and (f) 37.5μm, and the resin types were (a): Type B, (b): Type C, (c): Type B, (d): Type B, (e): Type C, and (f): Type B. The thicknesses of the ground and signal copper wiring were 12μm and 20μm, respectively, and the copper foil type was copper foil 1 for all.
[0107] [Example 3] 14, the thicknesses of the insulating resins were (A) 50 μm, (B) 50 μm, (C) 25 μm, (D) 25 μm, and (E) 50 μm, and the resin types were (A): Type A, (B): Type B, (C): Type A, (D): Type B, and (E): Type A. The thicknesses of the ground and signal copper wiring were 12 μm and 20 μm, respectively, and the copper foil type was copper foil 1 for all.
[0108] [Example 4] In the laminate shown in Fig. 15, the thicknesses of the insulating resins were (a) 50μm, (b) 25μm, (c) 50μm, (d) 50μm, (e) 25μm, and (f) 50μm, and the resin types were (a): Type B, (b): Type C, (c): Type B, (d): Type B, (e): Type C, and (f): Type B. The thicknesses of the ground and signal copper wiring were 12μm and 20μm, respectively, and the copper foil type was copper foil 1 for all.
[0109] <Parameters entered into the simulation software> The tensile modulus [GPa] and yield stress [MPa] of the parameters input into the simulation software for the insulating resin and copper foil 1 are shown in the following Table 1. The yield stress values were obtained from the stress-strain curves of FIGS.
[0110] [Table 1]
[0111] <List of results of Examples and Comparative Examples> The results obtained in Examples 1 to 4 and Comparative Example 1 are summarized in Table 2.
[0112] [Table 2]
[0113] <Summary> Comparing the FPCs of Examples 1 to 4 with the FPC of Comparative Example 1, the tensile modulus of the first resin film exceeds 7 GPa in the case of the FPC of Comparative Example 1. Therefore, compared to the FPCs of Examples 1 to 4 in which the tensile modulus of the first resin film is within the range of 0.9 to 7 GPa, the absolute value of the maximum strain (compression mode) is larger, and it can be determined that the 90-degree bending resistance is reduced.
[0114] Although the embodiment of the present invention has been described in detail above for the purpose of illustration, the present invention is not limited to the above embodiment, and various modifications are possible. [Explanation of symbols]
[0115] 1. First resin film 1a Polyimide layer (A) 1b Polyimide layer 1c Polyimide layer 2. Second resin film 2a Adhesive layer 2b Polyimide insulating layer 2b1 Polyimide layer 2b2 Polyimide layer 10 FPC G1 First ground layer G2 Second ground layer S Conductor Pattern
Claims
1. A flexible circuit board that is folded at approximately 90 degrees and stored in a housing of an electronic device, A first resin film; A conductive pattern formed on one surface of the first resin film; a first ground layer laminated on the other surface of the first resin film; a second resin film laminated on the conductive pattern forming surface side of the first resin film; a second ground layer laminated on a surface of the second resin film opposite to the first resin film, a thickness (L1) of the first resin film is within a range of 50 μm or more and 150 μm or less, a thickness (L2) of the second resin film is within a range of 50 μm or more and 150 μm or less, and a ratio (L2 / L1) of the thickness (L2) of the second resin film to the thickness (L1) of the first resin film is within a range of 0.8 or more and 1.2 or less, the first resin film has a polyimide layer (A) in a central layer, and the thickness of the polyimide layer (A) is in the range of 0.5 to 0.96 with respect to the total thickness of the first resin film; A flexible circuit board characterized in that the tensile modulus of elasticity (M1) of the first resin film is in the range of 0.9 GPa or more and 7 GPa or less, the tensile modulus of elasticity (M2) of the second resin film is in the range of 0.9 GPa or more and 7 GPa or less, and the ratio (M2 / M1) of the tensile modulus of elasticity (M2) of the second resin film to the tensile modulus of elasticity (M1) of the first resin film is in the range of 0.7 or more and 1.3 or less.
2. the second resin film has a polyimide insulating layer including a single or multiple polyimide layers and an adhesive layer; the adhesive layer is located between the polyimide insulating layer and a surface of the first resin film on which a conductor pattern is formed, 2. The flexible circuit board according to claim 1, wherein the adhesive layer has a tensile modulus of elasticity in the range of 0.2 GPa or more and 2 GPa or less.
3. A flexible circuit board as described in claim 1 or 2, wherein the second ground layer is bent at approximately 90 degrees so that it is on the outside.
Citation Information
Patent Citations
Method for manufacturing flexible wiring board
JP2011061059A
Flexible printed circuit, and method for manufacturing the same
JP2014207297A
Multi-layer transmission line plate
JP2018014390A
printed wiring board
JP6537172B2
Circuit board and method for manufacturing same
WO2016072361A1